Endovascular Treatment of Superior Vena Cava Obstruction After Surgical Correction of Intracardiac Total Anomalous Pulmonary Venous Connection. (April 2015) - Veshti, Altin; Prifti, Edvin; Ballerini, Luigi; Vanini, Vittorio
A three-month-old infant operated for obstructed intracardiac total anomalous pulmonary venous connection was readmitted because of sinus bradycardia and superior vena cava syndrome. Cardiac catheterization revealed a stenosis at the superior vena cava–right atrial junction with retrograde azygos flow. Following balloon dilatation of the stenotic area and stent implantation, the superior vena cava syndrome was rapidly relieved. At six months, an echocardiogram confirmed unobstructed flow from the superior vena cava to the right atrium.